How has the Zimbabwe mycobacterial culture and drug sensitivity testing system among re-treatment tuberculosis patients functioned during the scale-up of the Xpert MTB/RIF assay?. (10th July 2018) - Timire, Collins; Takarinda, Kudakwashe C; Harries, Anthony D; Mutunzi, Herbert; Manyame-Murwira, Barbara; Kumar, Ajay M V; Sandy, Charles
Abstract: Background: In Zimbabwe, while the Xpert MTB/RIF assay is being used for diagnosing tuberculosis and rifampicin-resistance, re-treatment tuberculosis (TB) patients are still expected to have culture and drug sensitivity testing (CDST) performed at national reference laboratories for confirmation. The study aim was to document the Xpert MTB/RIF assay scale-up and assess how the CDST system functioned for re-treatment TB patients. Methods: We performed an ecologic study using national aggregate data. Results: Use of the Xpert MTB/RIF assay increased from 11 829 to 68 153 between 2012 and 2016. Xpert assays worked well, with successful tests in more than 90% of cases, TB detection rates at 15–17% and rifampicin resistance in <10%. During Xpert scale-up, the number of sputum specimens from re-treatment TB patients reaching national reference laboratories for CDST increased from 12% to 51%. In terms of laboratory performance, culture contamination increased from 3% to 17%, positive cultures from 13% to 17% and successful CDST from 6% to 14%: the proportion of CDST showing any resistance to rifampicin averaged 44%. From 2009 to 2016, the proportion of notified re-treatment TB patients with successful CDST increased from <1% to 7%. Conclusions: While components of Zimbabwe's CDST system for re-treatment TB patients showed some changes during the scale-up of the Xpert MTB/RIF assay, overall performance was poor. The country must either invest in improving CDST performance or in advanced molecular diagnostic technology.